Analysis of the Climate Village Program as a Local Ecotourism Opportunity in Supporting Green Economic Development Planning - Saut Maruli Tua Pandiangan; Lalang Saksono; Aglis Andhita Hatmawan; Ramadhani Kirana Putra; Riezky Purnama Sari (LPPPIPublishing, 2026)
The purpose of this study is to analyze the climate village program as a local ecotourism opportunity in supporting green economic development planning. The research method used in this study is descriptive narrative research. The data analysis process used secondary data such as books and related journal articles. The research results show that converting the climate village program into a local ecotourism destination is a tactical and strategic step in green economic development planning. This approach successfully combines ecological interests through emission reduction and climate resilience with economic interests through community well-being in a harmonious manner. The climate village program is no longer viewed as a burdensome environmental program, but rather as a high-value economic asset that attracts the outside world while preserving the earth.